Impact of Dividend Policy on Stock Prices in Quoted Industrial Goods Companies in Nigeria - Ajadi, Oyekola Kamarudeen; Dewu, Umar Muhammed; Ayuba, Nathaniel (Kashere Journal of Management Sciences, 2024)
Selecting a suitable dividend policy is major hiccup decision for the industrial goods companies because flexibility to expand a business or to invest in future projects depends on the amount of dividends they paid their shareholders. Against this background this study aimed at determining the effect of dividend policy on stock prices of quoted industrial goods companies in Nigeria. Secondary data was collected from the period of 2013 to 2017 and analyzed with the aid of SPSS Version 21. Descriptive study research design was used to determine frequency of occurrence or extent to which variables were related. Simple OLS regression results reveal that, dividend policy has significant effect on stock prices of Quoted Industrial Goods Companies in Nigeria and that announcement of dividend is important to the shareholders because of its tax effect and information content. It is therefore recommended that, the Industrial Goods firms in Nigeria should consider the interest of shareholders in choosing dividend policies that will maximize shareholders’ value by management.